2012
DOI: 10.1186/1472-6963-12-11
|View full text |Cite
|
Sign up to set email alerts
|

Handover patterns: an observational study of critical care physicians

Abstract: BackgroundHandover (or 'handoff') is the exchange of information between health professionals that accompanies the transfer of patient care. This process can result in adverse events. Handover 'best practices', with emphasis on standardization, have been widely promoted. However, these recommendations are based mostly on expert opinion and research on medical trainees. By examining handover communication of experienced physicians, we aim to inform future research, education and quality improvement. Thus, our o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
1
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 30 publications
5
72
1
10
Order By: Relevance
“…I've found a lot of people at Chuck-E-Cheese or they're going to lunch, it's a common time for children's birthday parties." (Intensivist 12) (14). The authors of this study videotaped 40 attending handovers, noting poor conformation of these handoffs to any of three common communication schemes: SBAR (Situation, Background, Assessment, Recommendation), SOAP (Subjective, Objective, Assessment, Plan), or the format of a standard medical admission note.…”
Section: Box 2 Narrative Comments About Handoff Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…I've found a lot of people at Chuck-E-Cheese or they're going to lunch, it's a common time for children's birthday parties." (Intensivist 12) (14). The authors of this study videotaped 40 attending handovers, noting poor conformation of these handoffs to any of three common communication schemes: SBAR (Situation, Background, Assessment, Recommendation), SOAP (Subjective, Objective, Assessment, Plan), or the format of a standard medical admission note.…”
Section: Box 2 Narrative Comments About Handoff Practicesmentioning
confidence: 99%
“…In contrast, transitions of care at the attending physician level have been less well studied (10)(11)(12)(13). With the exception of one single-center study (14), the handoff practices of intensivists have not been reported, and we know of no descriptions of how attending handoffs ought to be conducted.…”
mentioning
confidence: 99%
“…An earlier observational study of critical care physicians also showed poor handoff communication skills in experienced clinicians. 27 These results are concerning if senior residents are expected to supervise actual patient handoffs performed by PGY-1 residents as suggested by other investigators. 5 Our findings also suggest that PGY-1 and PGY-2 residents were not able to accurately self-assess their handoff skills, with no correlation between objectively measured handoff skill and residents' self-confidence.…”
Section: Discussionmentioning
confidence: 84%
“…(11)(12)(13)(14) It has been suggested that communication flow during handover should be tailored to suit the structure of an institution and is dependent on processes such as provider transitions and trainee change of rotation. (13,15) Furthermore, anaesthetists and nurses often have different expectations regarding the content and timing of information transfer.…”
Section: Discussionmentioning
confidence: 99%